2017
DOI: 10.3126/kumj.v13i4.16835
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Associated Factors of Hypertension among Adults in Rural Nepal: A Community Based Study

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
15
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 20 publications
6
15
1
Order By: Relevance
“…The study revealed the significant association between age groups and hypertension with p value 0.003 which is consistent to the various studies where significant association was established at p value < 0.001. 21 -24 Male respondents had higher odds of being hypertensive compared to females (OR = 1.816; 95% CI = 1.074 -3.070) which is similar to the study from North West Tanzania, 22 Rural Nepal, 25 and central Nepal. 26 Literacy level of the respondent was also found to be significantly associated with hypertension which is in line with the study by Ntuli ST, 12 Dhungana RR, 21 Mosha NR, 22 and Saeed KMI.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The study revealed the significant association between age groups and hypertension with p value 0.003 which is consistent to the various studies where significant association was established at p value < 0.001. 21 -24 Male respondents had higher odds of being hypertensive compared to females (OR = 1.816; 95% CI = 1.074 -3.070) which is similar to the study from North West Tanzania, 22 Rural Nepal, 25 and central Nepal. 26 Literacy level of the respondent was also found to be significantly associated with hypertension which is in line with the study by Ntuli ST, 12 Dhungana RR, 21 Mosha NR, 22 and Saeed KMI.…”
Section: Discussionsupporting
confidence: 76%
“…27 While no significant association was found in the study by Sam T. Ntuli. 12 Recent study confirm that smoking status were significantly associated with high blood pressure similar result was obtained in a study from Afganistan, 23 Nairobi Kenya, 24 Rural Nepal, 25 Kathmandu valley, 28 Vietnam. 29 While no significant association was found in the study conducted by Koju et al 15 |Original Article…”
Section: Discussionsupporting
confidence: 76%
“…5 Various studies in different places and time showed different prevalence. [6][7][8][9][10][11] Studies also showed many people having high blood pressure did not know they have hypertension. 6,12 The study was aimed to measure hypertension prevalence among adults in Kirtipur municipality, and to explore the risk behaviours of people.…”
Section: Introductionmentioning
confidence: 99%
“…After analyzing all the prescriptions collected from different Heart care Centers of the Kathmandu Valley, we found most of the institutes followed the seventh report of the Joint National Committee. In general, our data showed that 74% of the prescriptions followed the JNC guidelines [12,13]. Cost analysis showed that 57% of patients were charged below 500 rupees per month for their treatment.…”
Section: Discussionmentioning
confidence: 74%